PENGEMBANGAN OBJEK WISATA SUNGAI GULAMO KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - fitrawan adrian; Zulkarnaini Zulkarnaini (Jurnal Penelitian Administrasi Publik, 2021)
ABSTRACT The Gulamo River is a natural tourist attraction located in Tanjung Alai Village, XIII Koto Kampar District, precisely in the Koto Panjang PLTA Lake Area. It is very important to develop a tourism object on the Gulamo river, District XIII Koto Kampar in order to promote tourism, increase tourist visits, improve the economy of the surrounding community, and be more focused and have a set goal. This study aims to determine the implementation of tourism development and to see the inhibiting factors for the development of the Gulamo river attraction, XIII Koto Kampar District, Kampar Regency. In carrying out research using the theory of Chopper et al. where tourism development policies are measured from five main components related to attractiveness, accessibility, amenities, supporting facilities, and institutions. This research method is a qualitative research with a case study approach in descriptive form. The results of this study indicate that development in terms of attractiveness has not been seen, this is because one of the activities that support the development of attractiveness, namely increasing infrastructure and infrastructure development through special allocation funds (DAK) has not been carried out properly. On the other hand, the implementation of the official Festival/Event has not been carried out because due to Covid-19 is increasing and dangerous, so the implementation that causes the crowd is temporarily suspended. The inhibiting factors are limited funds, land acquisition, and human resources. Keywords: Development, Tourism object, Gulamo river